Strategi Pemasaran Oleh Pengusaha Perempuan di Kabupaten Jember - Sholihin, Muhammad Rijalus (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Small and medium-sized micro-enterprises are the tip of the community for the welfare of the community, especially the development of information technology that is increasingly well used by every business actor.There are many ways that can be done in embarrassing businesses ranging from face-to-face manuals and online media as it is today, which really must be mastered by business people. The number of vegetable traders who seem to continue to grow is certain they have their own way of marketing every product they have, but sometimes the lack of mastery of information technology that is minimal makes them often lose competitiveness with those with information technology as it is today. Through this research, it is hoped that a good and correct marketing strategy will be found to develop the business carried out by women entrepreneurs of vegetable traders, especially in the Umbulsari District of Jember.